The Long-Term Outcomes for Patients with Budd-Chiari Syndrome Caused by Behcet’s Disease: A Case Series on the Results, from Cirrhosis to Death - Cansu, Dondu Uskudar (Hepat Mon, 2016)
BACKGROUND: Budd-Chiari syndrome, which is a rare complication of Behcet’s disease, carries a high mortality rate. OBJECTIVES: The aim of the study was to present our long-term follow up experience with patients suffering from Budd-Chiari syndrome due to Behcet’s disease. METHODS: The records of 402 patients with Behcet’s disease were evaluated retrospectively. To facilitate detection of the long-term complications caused by Budd-Chiari syndrome, the patients were evaluated via physical examinations, laboratory tests, imaging modalities, and endoscopy results. RESULTS: The data for 402 patients diagnosed with Behcet’s disease, who were followed up at our hospital over 16 years, were analyzed retrospectively. Five of these 402 patients (1.2%) were diagnosed as having Budd-Chiari syndrome. The patients with Budd-Chiari syndrome were aged between 23 and 54, and all five were male. The interval between the onset of Behcet’s disease and the development of Budd-Chiari syndrome ranged from 1 to 8 years. All the patients had combined venous occlusion (affecting the hepatic vein and inferior vena cava). Portal venous thrombosis was detected in only one patient (Case 1), who died 1 month after the diagnosis of Budd-Chiari syndrome. The survival time for the other four patients after the diagnosis of Budd-Chiari syndrome ranged from 4 to 16 years. During the long-term follow-up, hepatic masses were detected via radiological surveillance in Case 3 (in the form of large regenerative nodules) and Case 4 (nodular regenerative hyperplasia and cirrhosis). CONCLUSIONS: In our study, portal venous thrombosis was detected in the patient who died during the acute period only. A study including large numbers of Budd-Chiari-syndrome patients with Behcet’s disease and portal venous thrombosis would be helpful to determine the prognostic significance of portal venous thrombosis in Budd-Chiari-syndrome patients with Behcet’s disease. In addition, patients should be monitored regularly for the development of hepatic masses via a long-term surveillance program.